Discovery of Novel Lead in the Group of N-substituted Piperazine Ether Derivatives with Potential Histamine H3 Receptor Activity - J. Kuder, Kamil; Stachnik, Marta; Schunack, Walter; Szymanska, Ewa; Kiec-Kononowicz, Katarzyna (Medicinal Chemistry, 2014)
The search for novel lead from the group of various substituted N-piperazine ether derivatives was performed. Acyl- and pyridylpiperazine ethyl/propyl ethers were obtained via three different synthetic pathways. Affinity to histamine H3 receptor was established, as well as, for selected compounds, selectivity towards histamine H4R. Docking studies to the histamine H3R homology model strengthened the position of (4-(3-(4-(3-chlorobenzoyl)piperazin-1- yl)propoxy)phenyl)(cyclopropyl)methanone (compound 26) as a novel lead for further studies on histamine H3 receptor antagonist/inverse agonist.
Keywords: Acylpiperazine